Prophet Muhammad’s Strategies Against Islamophobia: Historical Lessons for Modern Societies - Muhammad Nadir; Khaliq Ahmad (Journal of Islamic Civilization and Culture Review, 2026)
This study examines the strategies employed by Prophet Muhammad to respond to hostility, misrepresentation, and social exclusion, and explores their relevance for addressing Islamophobia in contemporary societies. The research investigates how attitudes comparable to Islamophobia were managed during the Meccan and Medinan periods and identifies historically grounded lessons applicable to modern pluralistic contexts. Using a qualitative historical approach, the study analyzes primary Islamic sources including the Qur’an, Hadith literature, and classical Sirah works, supported by contemporary academic scholarship. The findings reveal that the Prophet’s responses to fear-driven hostility were structured around ethical patience, nonviolent engagement, dialogue, and community-centered responsibility. In the Meccan period, moral restraint and ethical conduct functioned as strategies for maintaining legitimacy under conditions of persecution. In the Medinan period, principles of pluralism, inclusive governance, and shared civic responsibility were institutionalized to manage diversity and social cohesion. The study argues that these strategies form a coherent framework for addressing prejudice and exclusion. By interpreting Prophetic experience through an analytical lens, this article contributes to contemporary Islamophobia scholarship and offers ethically grounded insights for promoting coexistence and social harmony in modern multicultural societies.